если х=2, то 2/(2+1) = 2/3
если х=-3, то -3/(-3+1) = -3/(-2) = 1,5
если х=1,5, то 1,5/(1,5+1) = 1,5/2,5 = 15/25 = 3/5 = 0,6
если х=1/3, то 1/3 : (1/3+1) = 1/3 : (4/3) = 1/3 * 3/4 = 1/4 = 0,25
если х=-0,1, то -0,1/ (-0,1+1) = 0,1/0,9 = 1/9
Пошаговое объяснение:
у= х/(х+1)
х=2; у = 2/3
х= 3; у= - 3/2
х=1,5; у = 0,6
х= 1/3; у = 1/4
х = -0,1; у = - 1/9
если х=2, то 2/(2+1) = 2/3
если х=-3, то -3/(-3+1) = -3/(-2) = 1,5
если х=1,5, то 1,5/(1,5+1) = 1,5/2,5 = 15/25 = 3/5 = 0,6
если х=1/3, то 1/3 : (1/3+1) = 1/3 : (4/3) = 1/3 * 3/4 = 1/4 = 0,25
если х=-0,1, то -0,1/ (-0,1+1) = 0,1/0,9 = 1/9
Пошаговое объяснение:
у= х/(х+1)
х=2; у = 2/3
х= 3; у= - 3/2
х=1,5; у = 0,6
х= 1/3; у = 1/4
х = -0,1; у = - 1/9